Psitacídeos (Aves: Psittaciformes) em praças de Uberlândia, MG: um estudo sobre a exploração de recursos no ambiente urbano - Marques, Carolina Prudente (2012)
Urbanization is a process of concentration of human population in cities, which gradually transforms the natural environment. Birds, especially psittacines (macaws, parrots and parakeets), are between the most sensitive birds to the impacts produced by urbanization. But despite the wealth of the Brazilian bird fauna and the intense pace of urbanization seen in the country, little is known about the effects of this process on bird species. The objectives were: identify the resources used for food and roost by the different parrot species found in ten public squares located within the urban area of Uberlândia, MG; describe behavioral aspects of this group; and define the foraging strategies employed by parrot species in the exploration of the urban environment. The parrot species were investigated by Focal-Animal Sampling and Ad libitum Sampling. Observations were conducted from May 2011 to December 2011, in three periods comprising from sunrise to sunset. In 480 hours of observation we recorded 278 feeding events. In total, were consumed 33 plant species by four species of psittacines (Aratinga aurea, Aratinga leucophthalma, Brotogeris chiriri and Diopsittaca nobilis). These parrots showed a generalist diet. The plant families with the highest numbers of species in the parrot s diet were Fabaceae, Bignoniaceae, and Arecaceae. The food items consumed were: fruit (pulp, pulp with seed or seed), flower, nectar, and leaf. The plant species that stood out in the parrot s diet were: Terminalia catappa, Syzygium cumini, Handroanthus sp. and Livistona chinensis. The parrot species exploited a wide range of food resources in the public squares of Uberlândia, which demonstrates the importance of green areas for the maintenance of this group in the urban environment.